hubungan Perilaku merokok di Dalam Rumah dan Peggunaan Obat Nyamuk Bakar dengan Kejadian ISPA Pada Balita di kelurahan Semarang, Kecamatan Banjarnegara, Kabupaten Banjarnegara - farah Debby Pangestika; Sigid Sudaryanto; Yamtana Yamtana (Poltekkes Kemenkes Yogyakarta, 2015)
The incidence of ARI among under five children in Indonesia is still high. It is presumed that oneof the causes is indoor pollution due to smoking and mosquito coils using. The purpose of thisresearch was to prove the relationship between both behaviors and ARI incidence among underfive children in Kelurahan Semarang Kecamatan Banjarnegara by conducting a case control study. There were 30 children for each groups and the data were collected by using questionnaireand were analysed by using Odds Ratio calculations at 95% confidence level to identify themagnitude of the risks. The results show that OR for indoor smoking is as much as 3,05 (95%CI: 1,05-8,84) with p-value less than 0,001; and OR for mosquito coils using is 3,14 (95% CI:1,07-9,27) with p-value less than 0,001, as well. It can be concluded that those two variables under study are risk factors for ARI incidence among under five children in the study site.